International Marketing Research: A Marketing Strategy Case Study with Inari Arctic Cosmetics - Gassama, Mariama (2020)
The topic of the thesis is to study an international market. The report is a case study based on a luxury Finnish/German start-up skincare company Inari Arctic Cosmetics. The company already has presences in the international market and is currently gaining momentum in both the local and international markets. The main aim of the thesis will be to study from a strategic analytical approach, the company’s potentials by entering the UK market. The possible risks and potentials of this product in the targeted markets are also key components to that the study is focusing on. The research will go into details of multiple aspects of the market situation, such as cosmetics trends, risk factors, consumers behaviour and attitude towards a perspective high-end skincare product. The current political and economic climate of the UK will be discussed in major sections of the thesis. The primary data will be collected using both qualitative and quantitative method. In addition to this, secondary data will be collected through online articles, studies and reports. From the data collected, a conclusion on the topic based on multiple factors, such as market potential, possible partnerships will be made. A strategic international market entry mode will also be determined from the data collected. The research will also present recommendations for future research on similar subject.